Hypokalemia and hyperkalemia: Two Sides of the Same Coin - Tavares,Joana (2022)
Abstract Introduction: Potassium (K+) is the main intracellular cation and is crucial for normal cellular function, especially during children’s development and growth course. Changes in the homeostatic mechanisms of potassium regulation can lead to hypokalemia or hyperkalemia. Objective: This study aimed to provide a narrative review of this common, yet complex, condition of the clinical practice. Development/Conclusion: A comprehensive knowledge of the physiology of potassium metabolism is required to diagnose and treat its disturbances. Nearly 98% of potassium is intracellular, with the concentration gradient maintained by the sodium (Na+)/K+ ATPase pump located in the plasma membrane of cells. Several mechanisms, as β-adrenergic tone, insulin, and acid-base status, interfere with potassium intracellular distribution, but it is the kidney that has the key role in determining the total body potassium content, as it is responsible for approximately 80% of its excretion. The causes of hypokalemia are a mirror of hyperkalemia. Although these are two different entities, both require prompt intervention. The rate of correction depends on the severity of symptoms, presence of changes in electrocardiogram, and time of development of the disorder.